2019
DOI: 10.1161/jaha.119.013501
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Early Duchenne Cardiomyopathy With Aldosterone Inhibition: Results of the Multicenter AIDMD Trial

Abstract: BackgroundDuchenne muscular dystrophy incurs nearly universal dilated cardiomyopathy by the third decade of life, preceded by myocardial damage and impaired left ventricular strain by cardiac magnetic resonance. It has been shown that (1) mineralocorticoid receptor antagonist therapy with spironolactone attenuated damage while maintaining function when given early in a mouse model and (2) low‐dose eplerenone stabilized left ventricular strain in boys with Duchenne muscular dystrophy and evident myocardial dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…Raman et al showed that also spironolactone added to background therapy is noninferior to eplerenone in preserving contractile function. These findings support early mineralocorticoid receptor antagonist therapy as effective and safe in a genetic disease with high cardiomyopathy risk [ 52 ].…”
Section: Therapeutic Strategy For Dcmsupporting
confidence: 60%
See 1 more Smart Citation
“…Raman et al showed that also spironolactone added to background therapy is noninferior to eplerenone in preserving contractile function. These findings support early mineralocorticoid receptor antagonist therapy as effective and safe in a genetic disease with high cardiomyopathy risk [ 52 ].…”
Section: Therapeutic Strategy For Dcmsupporting
confidence: 60%
“…Although in adult HF, the use of betablockers is mandatory when ventricular function declines, the same evidence in children is lacking. In recent years, some retrospective and non-randomized prospective studies have demonstrated the beneficial effect of BB therapy in patients with DMD/DCM [ 52 , 55 , 56 , 57 , 58 ], while in some others this positive effect was not observed [ 59 , 60 ]. Although most of the studies are retrospective including various ages, BB in adjunct to ACEi showed to improve 5-year and 7-year survival rates [ 58 ], and also improving ventricular function [ 56 ].…”
Section: Therapeutic Strategy For Dcmmentioning
confidence: 99%
“…In cardiac clinical trials in DMD patients, spironolactone nor eplerenone added to ACEi or ARB reduced blood pressure nor changed salt balance from baseline over 3 years compared to standard therapy alone. [21][22][23] Typical measurements of renal function by urine or serum creatine are not used in DMD because of the large amount of muscle breakdown, but cystatin C has been used to demonstrate normal renal function in DMD patients. 45,46 Therefore, although finerenone results in less worsening of renal function in chronic kidney disease, 31 specific investigations of renal function were not included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…While the optimal timing for initiation of treatment with aldosterone antagonists remains unknown, early initiation has been shown to offer effective and safe cardioprotection in mice 29 and DMD patients. [30][31][32] However, it is unclear whether the attenuation of cardiac systolic dysfunction by aldosterone antagonists reduces mortality from heart failure, and there are no specific treatment policies for DMD patients with advanced heart failure. Thus, mortality from heart failure is still a major problem despite the availability of contemporary cardio-protective therapies.…”
Section: Discussionmentioning
confidence: 99%